Solid electrolyte sheet and all-solid-state battery

CN122843502APending Publication Date: 2026-09-29TOYOTA JIDOSHA KK
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610372558.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2026-03-25
Publication Date
2026-09-29

AI Technical Summary

Benefits of technology

[0012]根据本发明的一个实施方式,可提供能够抑制电池电阻并且具有高强度的固体电解质片。根据本发明的另一实施方式,可提供电池电阻得到抑制并且具有高强度的全固态电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122843502A_ABST
    Figure CN122843502A_ABST
Patent Text Reader

Abstract

The present application relates to a solid electrolyte sheet and an all-solid-state battery. The solid electrolyte sheet includes: a support that is a nonwoven fabric having an average fiber diameter of greater than 6.0 μm and less than 16.0 μm, including a fiber collection portion in which a plurality of fibers are aggregated or fused; and a solid electrolyte supported by the support. The all-solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer includes the solid electrolyte sheet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to solid electrolyte sheets and all-solid-state batteries. Background Technology

[0002] As a type of lithium-ion secondary battery with excellent safety, all-solid-state batteries with a solid electrolyte layer are known. Japanese Patent Application Laid-Open No. 2024-18552 discloses a solid electrolyte sheet for use in a solid electrolyte layer. The solid electrolyte sheet disclosed in Japanese Patent Application Laid-Open No. 2024-18552 comprises a nonwoven fabric and a solid electrolyte disposed within the nonwoven fabric. The nonwoven fabric has a pore size of 15 μm or less, and the ratio of the pore size to the particle size of the solid electrolyte (pore size / particle size) is 5.0 or more. Summary of the Invention

[0003] For solid electrolyte sheets with nonwoven fabric as a support, while the strength of the membrane can be improved by using the support (nonwoven fabric), on the other hand, the ion conductivity is impaired because the nonwoven fabric is an insulating material. Japanese Patent Application Publication No. 2024-18552 describes a solid electrolyte sheet that, while suppressing battery resistance, also considers preventing short circuits even if metallic foreign matter is mixed into the all-solid-state battery, but it does not disclose the balance between battery resistance and strength.

[0004] This invention provides a solid electrolyte sheet capable of suppressing battery resistance and possessing high strength. This invention provides an all-solid-state battery with suppressed battery resistance and high strength.

[0005] The solid electrolyte sheet of the first aspect of the present invention includes: a support body, said support body being a nonwoven fabric having an average fiber diameter greater than 6.0 μm and less than 16.0 μm, including the fiber diameter of a fiber aggregate portion formed by the aggregation or fusion of multiple fibers; and a solid electrolyte supported by said support body.

[0006] In the solid electrolyte sheet of the first embodiment, the average fiber diameter can be 6.5 μm or more and 13.5 μm or less.

[0007] In the solid electrolyte sheet of the first embodiment, the solid electrolyte may comprise a sulfide solid electrolyte.

[0008] The strength of the solid electrolyte sheet of the first method can be above 1.0 N / 5 mm and below 3.0 N / 5 mm.

[0009] In the solid electrolyte sheet of the first embodiment, the volume fraction of the support relative to the volume of the solid electrolyte sheet can be 30% or less.

[0010] In the solid electrolyte sheet of the first type, the weight per unit area of ​​the support can be 1 g / m². 2 Above and 10g / m2 the following.

[0011] The second embodiment of the all-solid-state battery of the present invention includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer comprises the solid electrolyte sheet of the first embodiment described above.

[0012] According to one embodiment of the invention, a solid electrolyte sheet capable of suppressing battery resistance and having high strength can be provided. According to another embodiment of the invention, an all-solid-state battery with suppressed battery resistance and high strength can be provided. Attached Figure Description

[0013] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings, wherein the same reference numerals denote the same elements.

[0014] Figure 1 This is a schematic diagram illustrating the method for measuring the fiber diameter of the nonwoven fabric that serves as the support for the solid electrolyte sheet of the present invention.

[0015] Figure 2 This is a schematic cross-sectional view showing an example of the structure of the all-solid-state battery of the present invention.

[0016] Figure 3 This is a graph showing the relationship between the average fiber diameter, strength, and electrical resistance of the nonwoven fabric contained in the solid electrolyte sheet. Detailed Implementation

[0017] In this invention, the numerical range represented by “~” means the range containing the values ​​before and after “~” as the minimum and maximum values, respectively.

[0018] For the numerical ranges described in segments in this invention, the upper or lower limit value of a certain numerical range can be replaced by the upper or lower limit value of other numerical ranges described in segments. For the numerical ranges described in this invention, the upper or lower limit value of a certain numerical range can be replaced by the value shown in the embodiment. In this invention, a combination of two or more preferred methods is a more preferred method. In this invention, regarding the amount of each component, in the presence of two or more substances equivalent to that component, unless otherwise specified, it refers to the total amount of two or more substances. In this invention, the term "process" includes not only independent processes, but also processes that cannot be clearly distinguished from other processes, as long as the intended purpose of the process can be achieved. In this invention, "solid electrolyte" refers to an electrolyte that remains solid at 25°C under a nitrogen atmosphere.

[0019] solid electrolyte sheet

[0020] The solid electrolyte sheet of the present invention comprises a nonwoven fabric support and a solid electrolyte supported by the support. The support is a nonwoven fabric with an average fiber diameter greater than 6.0 μm and less than 16.0 μm, including the fiber diameter of the fiber aggregate portion formed by the aggregation or fusion of multiple fibers.

[0021] The solid electrolyte sheet of the present invention, due to its above-described structure, exhibits high strength and is able to suppress battery resistance. This effect is presumed to be based on the following reasons, but is not limited thereto.

[0022] The inventors of this invention have discovered that when using nonwoven fabric with the same fiber material and weight per unit area as a support for solid electrolyte sheets, the aggregation state of the fibers in the nonwoven fabric has a significant impact on the strength and resistance of the nonwoven fabric. It is believed that in the nonwoven fabric of the solid electrolyte sheet, fiber clusters existing in a planar direction due to fiber aggregation and fusion can locally reduce the filling capacity of the slurry. Furthermore, near the insulating fiber clusters, the resistance increases due to the detour path behavior of ions. In addition, regarding the strength of the solid electrolyte sheet, it is high when the fibers of the nonwoven fabric supporting the solid electrolyte are coarse or when the fibers are aggregated to a certain extent; when the fibers are too fine, the strength of the solid electrolyte sheet is compromised. The nonwoven fabric contains fiber aggregates formed by the aggregation or fusion of multiple fibers. While these fiber aggregates help improve the strength of the solid electrolyte sheet, they also hinder ion conduction in the solid electrolyte layer, leading to an increase in battery resistance. It is speculated that by setting the average fiber diameter, which is calculated by considering not only the fiber diameter of the individual fibers constituting the nonwoven fabric but also the fiber diameter of the fiber assembly as a single fiber, within a specified range, a solid electrolyte sheet that achieves a balance between increased strength and reduced resistance can be obtained. Furthermore, it is speculated that by using the solid electrolyte sheet of the present invention as the solid electrolyte layer in an all-solid-state battery, battery resistance can be reduced.

[0023] There are no particular limitations on the top view shape of solid electrolyte sheets; rectangles are an example. For a rectangle, squares, elongated rectangles, etc., can also be included.

[0024] The thickness of the solid electrolyte sheet depends on the thickness of the nonwoven fabric used as the support; it can be any thickness greater than or equal to that of the nonwoven fabric. From the viewpoint of further reducing battery resistance, the thickness of the solid electrolyte sheet is, for example, 50 μm or less, 30 μm or less, 20 μm or less, or 15 μm or less. The thickness of the solid electrolyte sheet is, for example, 1 μm or more or 10 μm or more. The thickness of the solid electrolyte sheet is preferably 1 μm to 50 μm.

[0025] support

[0026] The solid electrolyte sheet incorporates a nonwoven fabric as a support. Nonwoven fabric is a sheet-like material formed by bonding or entanglement of fibers without weaving; it is a planar fibrous assembly with a specified level of structural strength obtained through physical and / or chemical methods other than weaving, knitting, and papermaking (JIS L 0222:2022). Nonwoven fabric contains fiber assemblies formed by the aggregation or fusion of multiple fibers (monofibers). In this invention, the nonwoven fabric considers the fiber assemblies formed by the aggregation or fusion of monofibers as a single fiber, and the average fiber diameter, including the fiber diameter of the fiber assembly (sometimes referred to as "assembly fiber diameter" in this invention), is greater than 6.0 μm and less than 16.0 μm.

[0027] Figure 1 This is a schematic diagram illustrating the method for measuring the fiber diameter of nonwoven fabrics in this invention. The fiber diameter of the nonwoven fabrics in this invention is measured by observation using a scanning electron microscope (SEM) at 200x magnification (field of view: 0.5mm × 0.4mm). The 200x SEM image is shown below. Figure 1 The diagram shows six parallel and equally spaced straight lines L( Figure 1 Divide the area (represented by dashed lines) into 7 equal parts. Measure the length (fiber width) of all fiber groups that cross each straight line L. Fibers (monofibers) overlap 10 times to form a nonwoven fabric. Figure 1 In this diagram, 12A is the portion where multiple fibers 10 are aggregated, and 12B is the portion where multiple fibers 10 are fused together. Fiber aggregate portions 12A and 12B are formed by the aggregation of multiple single fibers 10, but each aggregate portion 12A and 12B is considered as a single fiber, and the fiber diameter of the aggregate portions 12A and 12B is measured (the length of the fiber group crossing the straight line L (fiber width), sometimes referred to as the "fiber aggregate diameter"). 12C is the state where the portion of the straight line L is crossed by a single fiber 10 (single fiber portion), and the fiber diameter of the single fiber 10 is measured here. Furthermore, the measured values ​​of fibers oriented parallel to the straight line L, i.e., the measured values ​​in the fiber length direction, are excluded. In this invention, the average value of the fiber diameters measured above is taken as the average fiber diameter.

[0028] From the viewpoint of the strength of the solid electrolyte sheet, the average fiber diameter of the nonwoven fabric can be 6.5 μm or more, 7.0 μm or more, or 8.0 μm or more. From the viewpoint of suppressing battery resistance, the average fiber diameter of the nonwoven fabric can be 13.5 μm or less, 12.0 μm or less, or 11.0 μm or less. The average fiber diameter of the nonwoven fabric is preferably 6.5 μm to 13.5 μm.

[0029] The average fiber diameter, including the diameter of the fiber assembly, can be controlled by the fiber type (material and single fiber diameter), dispersant (type and amount), nonwoven fabric weight per unit area, and manufacturing conditions of the solid electrolyte sheet (pressing pressure, temperature).

[0030] There is no particular limitation on the weight per unit area of ​​nonwoven fabric. From the viewpoint of the strength of solid electrolyte sheets, the weight per unit area of ​​nonwoven fabric is, for example, 1 g / m². 2 Above, 1.5g / m 2 Above or 2g / m 2 That's all. From the perspective of suppressing battery resistance, the weight per unit area of ​​nonwoven fabric is, for example, 10 g / m². 2 Below, 8g / m 2 Below or 6g / m 2 The preferred unit area weight of nonwoven fabric is 1 g / m². 2 ~10g / m 2 The method for determining the weight per unit area of ​​the nonwoven fabric is the same as that described in the examples.

[0031] The volume fraction of the nonwoven fabric relative to the volume of the solid electrolyte sheet (sometimes referred to in this invention as "volume fraction of nonwoven fabric in the solid electrolyte sheet" or "volume ratio of nonwoven fabric") is not particularly limited. The volume fraction of the nonwoven fabric in the solid electrolyte sheet is the percentage (%) of the volume of the nonwoven fabric relative to the total volume of the solid electrolyte sheet. From the viewpoint of the strength of the solid electrolyte sheet, the volume fraction of the nonwoven fabric in the solid electrolyte sheet is, for example, 8% or more, 10% or more, or 12% or more. From the viewpoint of suppressing battery resistance, the volume fraction of the nonwoven fabric in the solid electrolyte sheet is, for example, 30% or less, 28% or less, or 25% or less. The volume fraction of the nonwoven fabric in the solid electrolyte sheet is preferably 8% to 30%. The method for determining the volume fraction of the nonwoven fabric in the solid electrolyte sheet is the same as the method described in the examples.

[0032] The thickness of the nonwoven fabric is not particularly limited, for example, it is 5 μm to 50 μm. By making the thickness of the nonwoven fabric 5 μm to 50 μm, the solid electrolyte sheet can have higher strength, and the thickness of the solid electrolyte layer in the all-solid-state battery can be further reduced. As a result, the battery resistance can be further reduced. From the viewpoint of the strength of the solid electrolyte sheet, the thickness of the nonwoven fabric can be 7 μm or more, 10 μm or more, or 15 μm or more. From the viewpoint of further reducing battery resistance, the thickness of the nonwoven fabric can be 40 μm or less, 30 μm or less, or 20 μm or less. The method for measuring the thickness of the nonwoven fabric is the same as the method described in the examples.

[0033] There is no particular limitation on the type of nonwoven fabric. Examples include meltblown nonwoven fabric, spunbond nonwoven fabric, carded nonwoven fabric, parallel nonwoven fabric, cross-woven nonwoven fabric, random nonwoven fabric, spunbond nonwoven fabric, flash-spun nonwoven fabric, chemically bonded nonwoven fabric, spunlace nonwoven fabric, needle-punched nonwoven fabric, stitch-bonded nonwoven fabric, thermally bonded nonwoven fabric, burst fiber nonwoven fabric, towed open fiber nonwoven fabric, and membrane-split nonwoven fabric. Among these, thermally bonded nonwoven fabric is preferred. Thermally bonded nonwoven fabric has strong inter-fiber bonding and high strength even with low weight per unit area. As a result, it is easy to obtain nonwoven fabrics where not only the average fiber diameter, including the fiber diameter of the fiber assembly portion of this invention, is within the aforementioned range, but also the weight per unit area, volume fraction, and thickness are each within the aforementioned range.

[0034] There are no particular limitations on the diameter and length of the single fibers that make up nonwoven fabrics. Single fibers can be long or short. There are no particular limitations on the cross-sectional shape of single fibers; examples include circular, elliptical, and irregular shapes.

[0035] Examples of materials that constitute fibers include resins and glass. Examples of resins include polyester resins, polyolefin resins, polyamide resins, and polyimide resins. Examples of polyester resins include polyethylene terephthalate (PET). Examples of polyolefin resins include polyethylene (PE) and polypropylene (PP). Examples of polyamide resins include nylon and aramid.

[0036] solid electrolyte

[0037] The solid electrolyte sheet contains a solid electrolyte. The solid electrolyte is supported by a nonwoven fabric, which serves as a support. The solid electrolyte only needs to be supported by the nonwoven fabric; it can exist inside the nonwoven fabric, or it can be covered by the nonwoven fabric, or it can be uncovered.

[0038] The solid electrolyte can be in the form of particles, for example. The particle size (D50) of the solid electrolyte is preferably 3.0 μm or less. When the particle size of the solid electrolyte is 3.0 μm or less, the battery resistance is reduced compared to when the particle size is greater than 3.0 μm. The particle size of the solid electrolyte is preferably 0.05 μm or more, more preferably 0.2 μm or more, even more preferably 1.0 μm or more, and particularly preferably 2.0 μm or more. The particle size of the solid electrolyte is more preferably 2.8 μm or less, even more preferably 2.6 μm or less, and particularly preferably 2.4 μm or less. The particle size of the solid electrolyte is preferably 0.05 μm to 3.0 μm. The particle size of the solid electrolyte is preferably smaller than the thickness of the nonwoven fabric. The method for measuring the particle size of the solid electrolyte is the same as the method described in the examples.

[0039] As a solid electrolyte, it is preferred to include at least one solid electrolyte selected from the group consisting of sulfide solid electrolytes, oxide solid electrolytes and halide solid electrolytes.

[0040] As a sulfide solid electrolyte, it is preferable to contain sulfur (S) as the main component of the anionic element, and more preferably to contain elements such as Li, A, and S. The A element is selected from at least one of the group consisting of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In. The sulfide solid electrolyte may further contain at least one of O and a halogen element. Examples of halogen elements (X) include F, Cl, Br, and I. The composition of the sulfide solid electrolyte is not particularly limited, and examples include xLi₂S·(100-x)P₂S₅ (70≤x≤80) and yLiI·zLiBr·(100-yz)(xLi₂S·(1-x)P₂S₅) (0.7≤x≤0.8, 0≤y≤30, 0≤z≤30). The sulfide solid electrolyte may also have a composition represented by the following general formula (1).

[0041] Li 4-x Ge 1-x P x S4(0<x<1)…Formula (1)

[0042] In equation (1), at least a portion of Ge can be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. Furthermore, at least a portion of P can be substituted with at least one selected from the group consisting of Sb, Si, Sn, B, Al, Ga, In, Ti, Zr, V, and Nb. A portion of Li can be substituted with at least one selected from the group consisting of Na, K, Mg, Ca, and Zn. A portion of S can be substituted with a halogen. The halogen is at least one selected from F, Cl, Br, and I.

[0043] Sulfide solid electrolytes can use known materials, such as glass ceramics or sulfide-germanium ore type solid electrolytes. Sulfide solid electrolytes may, for example, contain materials selected from LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li... 10 GeP2S 12 Li4P2S6, Li7P3S 11It is at least one of the group consisting of Li3PS4, Li7PS6, and Li6PS5X (X = Cl, Br, I). From the viewpoint of early detection of seal failure, the sulfide solid electrolyte is preferably a sulfide solid electrolyte of the argillium sulfide type.

[0044] The sulfide-germanium ore type solid electrolyte contains Li, P, S, and X (where X is a halogen). Element X can be F, Cl, Br, or I. Element X can be one or more. As a compositional formula, for example, it can be denoted by the type of element X. 1 Element (halogen 1), X 2 The element (halogen 2) can be represented as Li. 7-y- z PS 6-y-z X 1 y X 2 z (y≥0, Z≥0, 1≤y+z≤1.8). Specific examples include Li6PS5Cl, Li6PS5Br, Li6PS5I, and Li6PS5Cl. 0.75 Br 0.25 Li6PS5Cl 0.5 Br 0.5 Li 5.75 PS 4.75 Cl 1.25 Li 5.5 PS 4.5 Cl 1.5 And so on, but not limited to these.

[0045] As an oxide solid electrolyte, it is preferable to contain oxygen (O) as the main anionic element. For example, it may contain Li, Q (Q represents at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, and S), and O. Examples of oxide solid electrolytes include garnet-type solid electrolytes, perovskite-type solid electrolytes, NASICON (sodium superionic conductor) type solid electrolytes, Li-PO4-based solid electrolytes, and Li-BO4-based solid electrolytes. For example, Li7La3Zr2O can be used as a garnet-type solid electrolyte. 12 Li 7-x La3(Zr 2-x Nb x )O 12 (0≤x≤2), Li5La3Nb2O 12Examples of perovskite-type solid electrolytes include (Li,La)TiO3, (Li,La)NbO3, and (Li,Sr)(Ta,Zr)O3. Examples of NASICON-type solid electrolytes include Li(Al,Ti)(PO4)3 and Li(Al,Ga)(PO4)3. Examples of Li-PO solid electrolytes include Li3PO4 and LiPON (a compound in which some of the O in Li3PO4 is replaced by N). Examples of Li-BO solid electrolytes include Li3BO3 and a compound in which some of the O in Li3BO3 is replaced by C.

[0046] As a halide solid electrolyte, a solid electrolyte containing Li, M, and X is preferred (M represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br). Specifically, Li is preferred. 6-3z Y z X6 (X represents Cl or Br, z satisfies 0 < z < 2), Li 6-(4-x)b (Ti 1- x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5). In Li 6-3z Y z Among X6, from the viewpoint of excellent lithium-ion conductivity, Li3YX6 (where X represents Cl or Br) is more preferred, and Li3YCl6 is even more preferred. Furthermore, from the viewpoint of suppressing the oxidative decomposition of sulfide solid electrolytes, Li... 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5) is preferably contained together with solid electrolytes such as sulfide solid electrolytes.

[0047] adhesive

[0048] Solid electrolyte sheets may or may not contain a binder. Examples of binders include rubber-based binders and fluorinated binders. Examples of rubber-based binders include butadiene rubber, hydrogenated butadiene rubber, styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, and ethylene propylene rubber. Examples of fluorinated binders include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene, and fluororubber. When the solid electrolyte contains a binder, the binder content relative to the total amount of the solid electrolyte can be 0 parts by mass to 3 parts by mass.

[0049] All-solid-state batteries

[0050] The all-solid-state battery of the present invention comprises a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer comprises the solid electrolyte sheet of the present invention.

[0051] The all-solid-state battery of the present invention, by having the above-described configuration, can achieve high strength and suppress battery resistance. The reasoning for presuming this effect is the same as that for the solid electrolyte sheet described above, but it is not limited thereto.

[0052] When the combination of the positive electrode layer, solid electrolyte layer, and negative electrode layer is considered as a single power generation unit, an all-solid-state battery can have only one power generation unit or more than two. When an all-solid-state battery has more than two power generation units, these units can be connected in series or in parallel.

[0053] solid electrolyte layer

[0054] The solid electrolyte layer comprises the solid electrolyte sheet of the present invention, or may consist solely of the solid electrolyte sheet of the present invention. The solid electrolyte layer is subjected to battery-like pressing.

[0055] From the perspective of further reducing battery resistance, the thickness of the solid electrolyte layer is 50 μm or less, 30 μm or less, 20 μm or less, or 15 μm or less. Alternatively, the thickness of the solid electrolyte layer may be 1 μm or more, or 10 μm or more. Preferably, the thickness of the solid electrolyte layer is between 1 μm and 50 μm.

[0056] The solid electrolyte layer has a history of undergoing battery-based pressing. Through battery-based pressing, both the nonwoven fabric and the solid electrolyte contained in the solid electrolyte sheet are less prone to deformation. Therefore, the nonwoven fabric and solid electrolyte contained in the solid electrolyte sheet after battery-based pressing can be considered to be the same as those contained in the solid electrolyte sheet before battery-based pressing.

[0057] The average fiber diameter of the nonwoven fabric contained in the solid electrolyte layer can be obtained, for example, by separating the nonwoven fabric from the solid electrolyte layer using an organic solvent, and then measuring and calculating the fiber diameter of the obtained nonwoven fabric using the same method as described above. The particle size of the solid electrolyte contained in the solid electrolyte layer can be obtained, for example, by observing the cross-section of the solid electrolyte layer using a scanning electron microscope (SEM), randomly selecting solid electrolyte particles, and measuring the average particle size.

[0058] The nonwoven fabric contained in the solid electrolyte layer may or may not be in direct contact with at least one of the positive and negative electrode layers. An additional solid electrolyte layer may be disposed between the nonwoven fabric contained in the solid electrolyte layer and at least one of the positive and negative electrode layers. By disposing of an additional solid electrolyte layer, the internal resistance of the all-solid-state battery can be reduced. The additional solid electrolyte layer contains a solid electrolyte and may also contain a binder if necessary. Examples of solid electrolytes and binders are the same substances exemplified as solid electrolytes and binders that can be included in the solid electrolyte sheet. The additional solid electrolyte layer generally does not have electronic conductivity. The additional solid electrolyte layer does not contain nonwoven fabric. The thickness of the additional solid electrolyte layer is not particularly limited.

[0059] Positive electrode layer

[0060] The positive electrode layer contains a positive electrode active material. The positive electrode layer may further contain at least one of a solid electrolyte, a conductive material, and a binder, depending on the requirements.

[0061] The positive electrode layer preferably contains a lithium composite oxide as the positive electrode active material. The lithium composite oxide may contain at least one element selected from the group consisting of F, Cl, N, S, Br, and I. Furthermore, the lithium composite oxide may have a crystal structure belonging to at least one space group selected from R-3m, Immm, and P63-mmc (also known as P63mc, P63 / mmc). Moreover, in the lithium composite oxide, the dominant arrangement of the transition metal, oxygen, and lithium may be an O2-type structure. Examples of lithium composite oxides having a crystal structure belonging to R-3m include those made of Li... x Me y O α X β (Me represents at least one compound selected from the group consisting of Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si, and P; X represents at least one compound selected from the group consisting of F, Cl, N, S, Br, and I, satisfying 0.5 ≤ x ≤ 1.5, 0.5 ≤ y ≤ 1.0, 1 ≤ α < 2, and 0 < β ≤ 1.) As lithium composite oxides having a crystal structure belonging to the Immm range, examples include those composed of Li x1 M 1 A 1 2(satisfying 1.5≤x1≤2.3, M) 1 Includes at least one selected from the group consisting of Ni, Co, Mn, Cu, and Fe, A 1 It contains at least oxygen, A 1 Composite oxides (specifically, Li₂NiO₂) are defined as having an oxygen content of 85 atomic percent or more.x1 M 1A 1-x2 M 1B x2 O 2- y A 2 y (0≤x²≤0.5, 0≤y≤0.3, at least one of x² and y is not 0, M) 1A It means that at least one of the following is selected from the group consisting of Ni, Co, Mn, Cu and Fe, M 1B The term A1 represents a composite oxide selected from the group consisting of at least one of Al, Mg, Sc, Ti, Cr, V, Zn, Ga, Zr, Mo, Nb, Ta, and W, and A2 represents at least one selected from the group consisting of F, Cl, Br, S, and P. Examples of lithium composite oxides having a crystal structure belonging to the P63-mmc group include M1. x M2 y O2 (M1 represents an alkali metal (preferably at least one of Na and K), M2 represents a transition metal (preferably at least one selected from the group consisting of Mn, Ni, Co and Fe), and x+y satisfies 0 < x+y ≤ 2) represents a composite oxide. Examples of lithium composite oxides with an O2-type structure include those made of Li. x [Li α (Mn a Co b M c ) 1-α O2 (0.5 < x < 1.1, 0.1 < α < 0.33, 0.17 < a < 0.93, 0.03 < b < 0.50, 0.04 < c < 0.33, M represents at least one selected from the group consisting of Ni, Mg, Ti, Fe, Sn, Zr, Nb, Mo, W and Bi) represents a composite oxide. As a specific example, Li can be cited. 0.744 [Li 0.145 Mn 0.625 Co 0.115 Ni 0.115 O2, etc.

[0062] Lithium iron phosphate (LiFePO4, LFP) and lithium manganese iron phosphate (LMFP) can also be used as the positive electrode active material layer.

[0063] The positive electrode layer preferably includes, in addition to the positive electrode active material, a solid electrolyte selected from the group consisting of sulfide solid electrolytes, oxide solid electrolytes, and halide solid electrolytes. More preferably, at least a portion of the surface of the positive electrode active material is coated with a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. LiNbO3 is preferably the solid electrolyte used to coat at least a portion of the surface of the positive electrode active material.

[0064] The positive electrode layer may contain conductive materials. Examples of conductive materials include carbon materials, metal particles, and conductive polymers. Examples of carbon materials include particulate carbon materials and fibrous carbon materials. Examples of particulate carbon materials include acetylene black (AB) and Ketjen black (KB). Examples of fibrous carbon materials include carbon nanotubes (CNTs) and carbon nanofibers (CNFs).

[0065] Solid electrolytes and binders used for the positive electrode layer can be the same substances as those exemplified as solid electrolytes and binders that can be included in solid electrolyte sheets.

[0066] The thickness of the positive electrode layer is not particularly limited, but is preferably 0.1 μm to 1000 μm.

[0067] All-solid-state batteries can further include a positive electrode current collector. The positive electrode current collector collects electricity from the positive electrode layer. It is positioned on the opposite side of the solid electrolyte layer, with the positive electrode layer as a reference. Materials for the positive electrode current collector include, for example, stainless steel, aluminum, nickel, iron, titanium, and carbon. The preferred positive electrode current collector is aluminum alloy foil or aluminum foil. Aluminum alloy foil and aluminum foil can also be manufactured using powder. The shape of the positive electrode current collector can be, for example, foil or mesh.

[0068] negative electrode layer

[0069] The negative electrode layer contains a negative electrode active material. Depending on the requirements, the negative electrode layer may also contain at least one of a solid electrolyte, a conductive material, and a binder. Examples of negative electrode active materials include Li-based, carbon-based, oxide-based, and Si-based active materials. Examples of Li-based active materials include metallic lithium and lithium alloys. Examples of carbon-based active materials include graphite, hard carbon, and soft carbon. Examples of oxide-based active materials include lithium titanate. Examples of Si-based active materials include elemental Si, Si alloys, and silicon oxide.

[0070] The shape of the negative electrode active material can be, for example, particulate. The particle size of the negative electrode active material is preferably 10 μm or more, more preferably 100 μm or more. The particle size of the negative electrode active material is preferably 50 μm or less, more preferably 20 μm or less. The particle size of the negative electrode active material is preferably 10 μm to 50 μm. The method for determining the particle size of the negative electrode active material is the same as the method described in the examples.

[0071] The conductive material, solid electrolyte, and binder used for the negative electrode layer can be the same substances as those exemplified as conductive materials, solid electrolytes, and binders that can be included in the positive electrode layer. The thickness of the negative electrode layer is not particularly limited, but is preferably 0.1 μm to 1000 μm.

[0072] All-solid-state batteries can further incorporate a negative electrode current collector. The negative electrode current collector collects current from the negative electrode layer. It is positioned on the opposite side of the solid electrolyte layer, with the negative electrode layer as a reference. Examples of materials for the negative electrode current collector include stainless steel, copper, nickel, and carbon. Examples of shapes for the negative electrode current collector include foil and mesh.

[0073] Battery structure

[0074] All-solid-state batteries have a stacked structure of positive electrode / solid electrolyte layer / negative electrode. The positive electrode has a positive active material layer and a current collector, and the negative electrode has a negative active material layer and a current collector. The solid electrolyte layer can be a single layer or a multilayer structure with two or more layers. Figure 2 This is a schematic cross-sectional view showing an example of an all-solid-state battery. An all-solid-state battery can, for example, have... Figure 2 The cross-sectional structure is shown. The solid electrolyte layer B is supported by a support (non-woven fabric) 117. The solid electrolyte layer B can be as follows: Figure 2 The two-layer structure shown. Figure 2 The all-solid-state battery shown has a negative electrode comprising a negative current collector 113 and a negative active material layer A, a solid electrolyte layer B, and a positive electrode comprising a positive current collector 115 and a positive active material layer C. The negative active material layer A comprises a negative active material 101, a conductive additive 105, and a binder 109. The positive active material layer C comprises a positive active material 103, a conductive additive 107, and a binder 111, with the surface of the positive active material 103 coated with an LTAF electrolyte or a LiNbO3 electrolyte. The all-solid-state battery can also be constructed by sealing the stacked end faces (sides) of the positive / solid electrolyte / negative electrode stacked structure with resin. The current collector of the electrode can also be constructed by distributing a buffer layer, an elastic layer, or a PTC (Positive Temperature Coefficient) thermistor layer on its surface.

[0075] outer body

[0076] All-solid-state batteries can further include an external casing. The external casing at least houses the aforementioned power generation unit. Examples of external casings include laminated casings and shell-type casings.

[0077] Constraint components

[0078] The all-solid-state battery may further include a confinement member. The confinement member applies a confinement pressure to the positive electrode layer, the solid electrolyte layer, and the negative electrode layer along the thickness direction. The confinement pressure is preferably 0.1 MPa or more, more preferably 1 MPa or more, and even more preferably 5 MPa or more. The confinement pressure is preferably 100 MPa or less, more preferably 50 MPa or less, and even more preferably 20 MPa or less. The confinement pressure is preferably between 0.1 MPa and 100 MPa.

[0079] use

[0080] The all-solid-state battery of the present invention is typically an all-solid-state lithium-ion secondary battery. All-solid-state batteries can be used as power sources for vehicles, electronic devices, and power storage. Examples of vehicles include electric four-wheeled vehicles, electric two-wheeled vehicles, gasoline vehicles, and diesel vehicles. Examples of electric four-wheeled vehicles include battery electric vehicles (BEVs), plug-in hybrid electric vehicles (PHEVs), and hybrid electric vehicles (HEVs). Examples of electric two-wheeled vehicles include electric motorcycles and electric-assisted bicycles. Examples of electronic devices include handheld devices (e.g., smartphones, tablets, audio players), portable devices (e.g., laptops, CD (CompactDisc) players), and mobile devices (e.g., power tools, business cameras). The all-solid-state battery of the present invention is preferably used as a power source for driving hybrid electric vehicles, plug-in hybrid electric vehicles, or battery electric vehicles.

[0081] The present invention will be described in more detail below through embodiments, but the present invention is not limited to these embodiments.

[0082] Determination methods

[0083] The methods for determining the physical properties of the materials in the examples and comparative examples are as follows.

[0084] Average fiber diameter of nonwoven fabric

[0085] A sheet of a certain area was cut from the nonwoven fabric. The sheet (observation area: 0.5 mm × 0.4 mm) was observed using a SEM at 200x magnification. In the 200x SEM image, the fiber diameter, including the fiber diameter of the fiber assembly portion, was measured using the aforementioned method. The average fiber diameter was calculated by averaging the fiber diameters.

[0086] Weight per unit area of ​​nonwoven fabric

[0087] A sheet of a certain area is cut from a nonwoven fabric. The weight per unit area is determined by calculating the mass of each unit area of ​​the sheet.

[0088] Strength of solid electrolyte sheets

[0089] A release film is overlapped on the coated surface of the solid electrolyte sheet, and then rolled at a pressure of 1 ton / cm to peel off the release film, producing an individual solid electrolyte sheet. The individual solid electrolyte sheet is cut into strips 5 mm wide × 5 cm long, and its tensile strength is determined by a tensile test. In this case, the longitudinal direction (MD) is used as the length direction for the test.

[0090] Particle size

[0091] The particle size of the solid electrolyte was determined using a laser diffraction particle size distribution measuring device. Specifically, the analyte was dispersed in a dispersion medium, and the particle size distribution on a volume basis was measured using the particle size distribution measuring device. The cumulative particle size distribution value on the volume basis, representing 50% of the particle size, was taken as the average particle size (D50).

[0092] Fabrication of nonwoven fabric (support)

[0093] By changing the fiber diameter (monofiber) of the fibers used in the production of nonwoven fabrics or the nonwoven fabric manufacturing process, PET nonwoven fabrics with different average fiber diameters, including the fiber diameter of the fiber assembly section, were produced. The average fiber diameters of the various nonwoven fabrics produced are shown in Table 1.

[0094] Example 1

[0095] Production of solid electrolyte sheets containing non-woven fabric

[0096] Using PET fibers with a single fiber diameter of 5μm, a unit area weight of 3g / m² is produced. 2 The nonwoven fabric is used as a support for the solid electrolyte. A solid electrolyte sheet containing the nonwoven fabric is fabricated using the nonwoven fabric prepared above. In this case, the longitudinal direction of the nonwoven fabric is used as the coating flow direction. A Li₂S-P₂S₅ glass-ceramic solid electrolyte with an average particle size (D50) of 1 μm is used as the sulfide solid electrolyte.

[0097] SBR (styrene-butadiene rubber) binder, at 3% by mass relative to the sulfide solid electrolyte, was weighed and incorporated into tetrahydronaphthalene to achieve a solid content of 40% by mass. The mixture was then ultrasonically dispersed for 1 minute using an ultrasonic dispersion device to obtain a solid electrolyte paste. Next, a nonwoven fabric was placed on a 25 μm thick release film (Si-coated PET film), and the resulting solid electrolyte paste was coated using a commercially available coater to achieve a weight per unit area of ​​3.0 mg / cm². 2The coating is applied evenly. Then, the coating is dried at 100°C for 60 minutes to obtain a solid electrolyte sheet containing nonwoven fabric on a release film. The volume ratio of the nonwoven fabric relative to the solid electrolyte sheet is calculated from the unit area weight and specific gravity of the solid electrolyte and the nonwoven fabric.

[0098] Fabrication of the positive electrode layer

[0099] LiNi with an average particle size (D50) of 3 μm was used as the positive electrode active material. 0.8 Co 0.15 Al 0.05 O2 powder. LiNbO3 was coated onto the surface of the positive electrode active material using a sol-gel method. The same material as the solid electrolyte sheet was used as the solid electrolyte. The positive electrode active material and sulfide solid electrolyte were weighed to achieve a mixing ratio of "positive electrode active material / sulfide solid electrolyte = 7 / 3 (volume ratio)". 3% by mass of conductive material (VGCF) relative to the positive electrode active material was weighed. 1% by mass of SBR (styrene-butadiene rubber) binder was further weighed, and these were incorporated into tetrahydronaphthalene to achieve a solid content of 65% by mass. Ultrasonic dispersion was performed for 1 minute using an ultrasonic dispersion device to obtain a composition (positive electrode paste) for forming the positive electrode active material layer. The obtained positive electrode paste was then coated using a doctor blade of a commercially available coater to achieve a weight per unit area of ​​12 mg / cm². 2 The coating was uniformly applied to a 15 μm thick aluminum foil positive current collector. Then, the coating was dried at 100°C for 60 minutes to obtain a positive electrode with a positive active material layer formed on the aluminum foil positive current collector.

[0100] Fabrication of the negative electrode layer

[0101] Li₄Ti₅O₂ with an average particle size (D50) of 1 μm was used as the negative electrode active material. 12 Powder, as a sulfide solid electrolyte, was prepared using Li2S-P2S5-based glass-ceramics. The negative electrode active material and sulfide solid electrolyte were weighed to achieve a mixing ratio of "negative electrode active material / sulfide solid electrolyte = 6 / 4 (volume ratio)". 1% by mass of conductive material (VGCF) was weighed. 2% by mass of SBR (styrene-butadiene rubber) binder was further weighed. These negative electrode active materials, sulfide solid electrolyte, conductive material, and SBR were then incorporated into tetrahydronaphthalene to achieve a solid content of 60% by mass. Ultrasonic dispersion was performed for 1 minute using an ultrasonic dispersion device to obtain a composition (negative electrode paste) for forming the negative electrode active material layer. The resulting negative electrode paste was then applied using a doctor blade of a commercially available coater to achieve a weight per unit area of ​​19 mg / cm². 2The coating is uniformly applied to a 20 μm thick surface-roughened Ni foil anode current collector. The coating is then dried at 100°C for 60 minutes to obtain a negative electrode with a battery-grade negative electrode active material layer formed on the surface-roughened Ni foil anode current collector.

[0102] Fabrication of all-solid-state batteries

[0103] A solid electrolyte sheet of the same shape was stacked on the Ni foil of the negative electrode layer and pressed at a pressure of 1 ton / cm. Next, the release film attached to the solid electrolyte layer stacked on the negative electrode was peeled off, and the positive electrode, along with the aluminum foil, was stacked on the solid electrolyte layer stacked on the negative electrode and pressed at a pressure of 4 ton / cm. The resulting stacked electrode body was then sealed with an outer casing made of an aluminum laminate pre-positioned with positive and negative terminals to fabricate the experimental all-solid-state battery (all-solid-state lithium-ion secondary battery) of Example 1.

[0104] Example 2

[0105] Adjust the dispersion dosage to improve fiber dispersibility, producing a unit area weight of 5 g / m². 2 The PET nonwoven fabric was used. A solid electrolyte sheet was prepared using the same method as in Example 1, except that the PET nonwoven fabric was used as the support. In addition to using the solid electrolyte sheet prepared above, the experimental all-solid-state battery (all-solid-state lithium-ion secondary battery) of Example 2 was prepared using the same method as in Example 1.

[0106] Example 3

[0107] Except for using PET fibers with a single fiber diameter of 3 μm, PET nonwoven fabric, solid electrolyte sheet, and the experimental all-solid-state battery (all-solid-state lithium-ion secondary battery) of Example 3 were prepared by the same method as in Example 1.

[0108] Comparative Example 1

[0109] In the production of nonwoven fabric, the fibers are fused together using a stronger pressing pressure than in Example 1, resulting in a unit area weight of 4 g / m². 2 The PET nonwoven fabric was used, except that the PET nonwoven fabric was prepared by the same method as in Example 1. The all-solid-state battery (all-solid-state lithium-ion secondary battery) for Comparative Example 1 was prepared by the same method as in Example 1, except that the prepared PET nonwoven fabric was used.

[0110] Comparative Example 2

[0111] In the production of nonwoven fabrics, PET fibers with a single fiber diameter of 2μm are used, resulting in a unit area weight of 4g / m². 2The PET nonwoven fabric was used, except that the PET nonwoven fabric was prepared by the same method as in Example 1. The all-solid-state battery (all-solid-state lithium-ion secondary battery) for Comparative Example 2 was prepared by the same method as in Example 1, except that the prepared PET nonwoven fabric was used.

[0112] Battery Review

[0113] Battery resistance measurement

[0114] For each experimental all-solid-state battery, constant current-constant voltage charging and discharging at a 1 / 3C rate was performed at an upper limit voltage of 4.4V and a lower limit voltage of 1.6V for two cycles. Afterwards, the SOC (State of Charge) was adjusted to 20% at a 1 / 3C rate. (The last sentence appears to be incomplete and possibly refers to a different process.) 6 The AC impedance was measured at Hz, and the value at the intersection of the Cole-Cole plot and the real axis was taken as the resistance. The measurement results are shown in Table 1.

[0115] [Table 1]

[0116] Figure 3 This is a graph showing the relationship between the average fiber diameter of the nonwoven fabric contained in the solid electrolyte sheets produced in the examples and comparative examples and the strength and resistance of the solid electrolyte sheets. Regarding the solid electrolyte sheets of Examples 1-3, the average fiber diameter of the nonwoven fabric serving as the support, including the fiber diameter of the fiber aggregate portion, is greater than 6.0 μm and less than 16.0 μm. These solid electrolyte sheets have a strength of 1.0 N / 5 mm or more and 3.0 N / 5 mm or less, and a resistance of 10.0 Ω or less (in...). Figure 3 Within the range enclosed by S, the balance between strength and resistance is excellent.

[0117] On the other hand, regarding the solid electrolyte sheet of Comparative Example 1, the average fiber diameter of the nonwoven fabric is 16.0 μm or more, and the strength of the solid electrolyte sheet is in the range of 1.0 N / 5 mm or more and 3.0 N / 5 mm or less, which is good; however, the resistance of the all-solid-state battery exceeds 10.0 Ω. Regarding the solid electrolyte sheet of Comparative Example 2, the average fiber diameter of the nonwoven fabric is 6.0 μm or less, and the resistance of the all-solid-state battery is 10.0 Ω or less, which is good; however, the strength of the solid electrolyte sheet is 0.1 N / 5 mm, which is insufficient.

[0118] The following illustrates some embodiments of the present invention. However, the embodiments of the present invention are not limited to these.

[0119] <1> A solid electrolyte sheet comprises: a support body, the support body being a nonwoven fabric having an average fiber diameter greater than 6.0 μm and less than 16.0 μm, including the fiber diameter of a fiber assembly comprising multiple fibers aggregated or fused together; and a solid electrolyte supported by the support body.

[0120] <2> according to <1> The solid electrolyte sheet wherein the average fiber diameter is 6.5 μm or more and 13.5 μm or less.

[0121] <3> according to <1> or <2> The solid electrolyte sheet, wherein the solid electrolyte comprises a sulfide solid electrolyte.

[0122] <4> according to <1> ~ <3> The solid electrolyte sheet according to any one of the following methods has a strength of 1.0 N / 5 mm or more and 3.0 N / 5 mm or less.

[0123] <5> according to <1> ~ <4> The solid electrolyte sheet according to any one of the following methods, wherein the volume fraction of the support relative to the volume of the solid electrolyte sheet is 30% or less.

[0124] <6> according to <1> ~ <5> In any one of the solid electrolyte sheets, the weight per unit area of ​​the support is 1 g / m². 2 Above and 10g / m 2 the following.

[0125] <7> An all-solid-state battery includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer comprises... <1> ~ <6> The solid electrolyte sheet as described in any one of the following.

Claims

1. A solid electrolyte sheet, characterized in that, Include: A support body, wherein the support body is a nonwoven fabric having an average fiber diameter greater than 6.0 μm and less than 16.0 μm, including the fiber diameter of a fiber assembly formed by the aggregation or fusion of multiple fibers; and A solid electrolyte supported by the support body.

2. The solid electrolyte sheet according to claim 1, characterized in that, The average fiber diameter is above 6.5 μm and below 13.5 μm.

3. The solid electrolyte sheet according to claim 1 or 2, characterized in that, The solid electrolyte includes a sulfide solid electrolyte.

4. The solid electrolyte sheet according to claim 1 or 2, characterized in that, Strength is above 1.0N / 5mm and below 3.0N / 5mm.

5. The solid electrolyte sheet according to claim 1 or 2, characterized in that, The volume fraction of the support relative to the volume of the solid electrolyte sheet is 30% or less.

6. The solid electrolyte sheet according to claim 1 or 2, characterized in that, The weight per unit area of ​​the support is 1g / m² 2 Above and 10g / m 2 the following.

7. An all-solid-state battery, characterized in that, The device comprises a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the solid electrolyte layer comprises the solid electrolyte sheet according to claim 1 or 2.

Citation Information

Patent Citations

  • Solid electrolyte sheet and all-solid battery

    JP2024018552A